Optimizing cadmium mitigation from Tunisian phosphates via chlorination-assisted calcination: A DoE and RSM approach - Marwa Mlaouah; Mohamed Karim Hajji; Oumayma Hamlaoui; Afef Barhoumi; Wided Bouguerra (Results in Engineering)
In response to growing environmental and health concerns, and in line with new European Parliament regulations on cadmium limits in phosphate fertilizers, this study focuses on improving cadmium removal from sedimentary phosphate ores. To address this issue, a two-phase experimental design approach was adopted. A full factorial design (2k) was used to efficiently identify the most influential factors and their interactions. This screening phase was followed by response surface methodology (RSM) using a Box-Behnken design to determine the optimal operating conditions. Among the investigated parameters, temperature and its interaction with the chlorinating agent were identified as key contributors to cadmium removal performance.The optimization process revealed that a maximum cadmium removal efficiency of 88.2% was achieved at 720–800°C with 20 wt% of chlorinating agent and a treatment time of 3 hours—representing a 15% reduction in temperature compared to conventional processes. A more energy-efficient protocol was also demonstrated, achieving a 58% reduction in cadmium content using 10 wt% of agent for 1 hour at 800°C. The quadratic model was statistically validated via ANOVA, confirming its robustness.Importantly, treatments using 10 wt% of NH4Cl or CaCl2 for 1 hour at 800°C preserved the phosphate's reactivity, ensuring its suitability for producing soluble fertilizers compliant with EU regulations. This work offers an effective and sustainable strategy for cadmium reduction in phosphates, balancing technical performance with regulatory and environmental requirements.